Lithium metal anode and electrochemical devices comprising the same

CN117280496BActive Publication Date: 2026-10-09LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380011437.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-01-12
Filing Date
2023-01-12
Publication Date
2026-10-09
Estimated Expiration
2043-01-12

AI Technical Summary

Technical Problem

于是加速了电池的劣化

Benefits of technology

[0012] To address the aforementioned problems, according to one aspect of the present invention, a lithium metal anode with the following embodiments is provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117280496B_ABST
    Figure CN117280496B_ABST
Patent Text Reader

Abstract

The present invention relates to a lithium metal anode and a method of manufacturing the same, the lithium metal anode comprising: a lithium metal layer; and an oxide layer on at least one surface of the lithium metal layer, wherein the oxide layer has a crack region and a non-crack region. By having the crack region on the oxide layer on at least one surface of the lithium metal layer, the battery life can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a lithium metal anode and an electrochemical device comprising the same.

[0002] This application claims priority and benefit to Korean Patent Application No. 10-2022-0004911, filed on January 12, 2022, with the Korean Patent Office, the disclosure of which is incorporated herein by reference in its entirety. Background Technology

[0003] With increasing attention being paid to energy storage technology, its applications have expanded to power mobile phones, tablets, laptops, and cameras, and even electric vehicles and hybrid electric vehicles. In addition, research and development of electrochemical devices are gradually increasing. Electrochemical devices are attracting significant attention in this area, and recently, research and development have been undertaken to improve the capacity density and specific energy of these batteries, focusing on new electrode and battery designs.

[0004] Among these electrochemical devices, lithium metal secondary batteries using lithium metal as the negative electrode, such as lithium-sulfur batteries (Li-S batteries), have a high theoretical capacity of 3,862 mAh / g and are attracting attention as next-generation high-capacity batteries due to the use of light lithium metal as the negative electrode active material. In lithium-sulfur batteries, sulfur reduction and lithium metal oxidation occur during discharge, and under these conditions, sulfur is converted from the cyclic structure of S8 to lithium polysulfides (LiPS) with a linear structure. Furthermore, lithium-sulfur batteries exhibit a stepped discharge voltage until the polysulfides are completely reduced to Li2S.

[0005] However, in lithium metal secondary batteries such as lithium-sulfur batteries, the charging / discharging efficiency is reduced and the battery life is degraded due to the side reactions of the electrolyte solution (deposition of byproducts caused by the decomposition of the electrolyte solution) and the instability of lithium metal (short circuits caused by the growth of dendrites on the lithium metal anode) during the charging / discharging process.

[0006] In particular, lithium metal, as the negative electrode active material, tends to form large-area dendrites and reacts with salts and additives in the electrolyte solution to form a solid electrolyte interface (SEI), thereby continuously consuming the salts and additives in the electrolyte solution. This accelerates battery degradation.

[0007] Therefore, in order to use lithium metal as the negative electrode, it is necessary to develop technologies that suppress dendrite growth and prevent the depletion of salt and additives in the electrolyte solution. Summary of the Invention

[0008] Technical issues

[0009] The present invention aims to provide a lithium metal anode and an electrochemical device comprising the same, wherein an oxide layer with cracked regions is formed on the surface of the lithium metal anode to improve lithium insertion / extraction, thereby enabling uniform electrodeposition and suppressing dendrite growth.

[0010] The present invention further aims to provide a method for preparing a lithium metal anode, wherein an oxide layer with cracked regions is formed on the surface of the lithium metal anode to improve lithium insertion / extraction, so that electrodeposition can occur uniformly and dendrite growth is suppressed.

[0011] Technical solution

[0012] To address the aforementioned problems, according to one aspect of the present invention, a lithium metal anode with the following embodiments is provided.

[0013] According to a first embodiment, a lithium metal anode comprises: a lithium metal layer; and an oxide layer on at least one surface of the lithium metal layer, wherein the oxide layer has cracked regions and non-cracked regions.

[0014] According to the second embodiment, in the first embodiment, the area ratio of the cracked region to the non-cracked region can be 2:8 to 9:1.

[0015] According to the third embodiment, in the first or second embodiment, the thickness of the oxide layer having the crack region can be equal to or less than 50% of the maximum thickness of the oxide layer.

[0016] According to the fourth embodiment, in any one of the first to third embodiments, the thickness of the oxide layer having the crack region can be from 10 nm to 10 μm.

[0017] According to the fifth embodiment, in any one of the first to fourth embodiments, the thickness of the lithium metal layer can be from 1 μm to 200 μm.

[0018] According to a sixth embodiment, a method for manufacturing a lithium metal anode according to any one of the first to fourth embodiments is provided, the lithium metal anode comprising a lithium metal layer and an oxide layer on at least one surface of the lithium metal layer, the method comprising forming a crack region in the oxide layer.

[0019] According to the seventh embodiment, in the sixth embodiment, the formation of the crack zone may include heat-treating the lithium metal anode in a vacuum atmosphere at a pressure of 0.001 to 1 Torr.

[0020] According to the eighth embodiment, in the sixth or seventh embodiment, the formation of the crack zone may include heat-treating the lithium metal anode in an inert atmosphere.

[0021] According to the ninth embodiment, in any of the sixth to eighth embodiments, the formation of the crack zone may include heat-treating the lithium metal anode at a temperature of 40°C to 120°C.

[0022] According to the tenth embodiment, in any of the sixth to ninth embodiments, the formation of the crack zone may include heat-treating the lithium metal anode at 65°C to 85°C.

[0023] According to the eleventh embodiment, an electrochemical device is provided, which includes a lithium metal anode as described in any one of the first to fifth embodiments.

[0024] According to the twelfth embodiment, in the eleventh embodiment, the electrochemical device may include a lithium secondary battery.

[0025] According to the thirteenth embodiment, in the twelfth embodiment, the lithium secondary battery may include at least one of a lithium-ion battery, a lithium-sulfur battery, or a lithium-lithium symmetric cell.

[0026] Beneficial effects

[0027] In a lithium metal anode of one embodiment of the present invention, since the crack region is formed in the oxide layer on the surface of the lithium metal, the lithium insertion / extraction can be improved by the crack region, and the surface area of ​​the lithium metal can be increased, thereby enabling electrodeposition to occur uniformly and suppressing dendrite growth.

[0028] In an electrochemical device incorporating a lithium metal anode according to one embodiment of the present invention, the lifespan can be improved because the lithium metal anode contains an oxide layer with cracked regions on its surface. Attached Figure Description

[0029] The accompanying drawings illustrate exemplary embodiments of the present invention and, together with the foregoing disclosure, are intended to provide a further understanding of the technical aspects of the present invention. Therefore, the present invention should not be construed as being limited to the drawings.

[0030] Figure 1 The image shows scanning electron microscope (SEM) images of the surface of the lithium metal anodes manufactured in Examples 1-3.

[0031] Figure 2 SEM images of the surface of the lithium metal anode manufactured in Comparative Example 1-1 are shown.

[0032] Figure 3 A graph illustrating the cycle life performance of the lithium-lithium symmetric cell of Example 2-1 is shown.

[0033] Figure 4 A graph illustrating the cycle life performance of the lithium-lithium symmetric cell manufactured in Example 2-2 is shown.

[0034] Figure 5 The graph illustrates the cycle life performance of the lithium-lithium symmetric cells manufactured in Examples 2-3.

[0035] Figure 6 The graph shows the cycle life performance of the lithium-lithium symmetric cells manufactured in Examples 2-4.

[0036] Figure 7 The graph illustrates the cycle life performance of the lithium-lithium symmetric cells manufactured in Examples 2-5.

[0037] Figure 8 A graph showing the cycle life performance of the lithium-lithium symmetric cell manufactured in Comparative Example 2-1 is provided.

[0038] Figure 9 The graph shows the cycle life performance of the lithium-sulfur batteries manufactured in Examples 3-1 to 3-5 and Comparative Example 3-1.

[0039] Figure 10 This is a cross-sectional view of a lithium metal anode according to one embodiment of the present invention.

[0040] Figure 11 This is a cross-sectional view of a lithium metal anode according to one embodiment of the present invention. Detailed Implementation

[0041] Exemplary embodiments of the present invention will be described in detail below. Before the description, it should be understood that the terms or words used in the specification and appended claims should not be construed as limited to their general or dictionary meanings, but rather should be interpreted according to their meanings and concepts corresponding to the technical aspects of the present invention, based on the principle of allowing the inventors to appropriately define the terms to obtain the best interpretation.

[0042] Therefore, the description of the embodiments is for illustrative purposes and not intended to limit the technical aspects of the invention, and it should therefore be understood that various other equivalents or modifications are possible at the time of filing this application.

[0043] When lithium metal is exposed to air, an oxide layer forms on its surface, depending on the type of gas present, such as Li₂CO₃, Li₂O, or LiOH. This oxide layer causes uneven current density on the lithium metal surface, reduces the surface area required for lithium ion dissolution and deposition, and acts as a resistive layer, decreasing ionic conductivity. Furthermore, the oxide layer leads to non-uniform lithium deposition.

[0044] The form of deposited lithium is related to the charge / discharge current density, the type of electrolyte, and whether lithium grows in a dendritic, moss-like, or spherical manner. Some dendritic lithium is stripped away during discharge to form dead lithium, which is electrochemically inactive but chemically highly reactive. Due to the formation of dead lithium, reversible charging and discharging of lithium is hindered when lithium metal is used as the negative electrode. Therefore, even in non-aqueous electrolytes, lithium metal exhibits poor electrode lifetime characteristics and low thermal stability.

[0045] The inventors have discovered that the above-mentioned problem can be solved by forming crack regions in the oxide layer present on the surface of lithium metal, and thus the present invention is completed.

[0046] One aspect of the present invention provides a lithium metal anode comprising a lithium metal layer and an oxide layer on at least one surface of the lithium metal layer, wherein the oxide layer has cracked regions and non-cracked regions.

[0047] Lithium metal can be lithium or a lithium alloy. In this case, the lithium alloy may contain lithium and an element capable of alloying with lithium, specifically at least one selected from the group consisting of Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, and Al.

[0048] The lithium metal anode may further include a current collector on one side of the lithium metal layer. The current collector can be a negative electrode current collector. The negative electrode current collector is not limited to a specific type and includes those with high conductivity that do not cause chemical changes in the battery. It can be selected from the group consisting of copper, aluminum, stainless steel, zinc, titanium, silver, palladium, nickel, iron, chromium, their alloys, and combinations thereof. Stainless steel can be surface-treated with carbon, nickel, titanium, or silver. Alloys can include aluminum-cadmium alloys, and may also include sintered carbon, non-conductive polymers surface-treated with conductive materials, or conductive polymers. A copper thin film is typically used as the negative electrode current collector.

[0049] Furthermore, various forms can be used, such as films, sheets, foils, meshes, porous bodies, foams, nonwoven fabrics, etc., with or without fine texture on their surfaces. Additionally, the thickness of the negative electrode current collector can range from 3 to 500 μm. When the thickness of the negative electrode current collector meets the above range, current collection efficiency can be achieved, and processability in the folding assembly process of the battery cell can be guaranteed.

[0050] The lithium metal layer can be in the form of a sheet or foil. In some cases, lithium or lithium alloys can be deposited or coated onto the current collector by a dry process, or granular lithium or lithium alloys can be deposited or coated by a wet process.

[0051] During the rolling process of lithium metal anodes, lithium metal may be exposed to oxygen or react with lubricants, resulting in the formation of a thick oxide layer on the lithium metal surface.

[0052] One aspect of the present invention provides a lithium metal anode comprising: a lithium metal layer; and an oxide layer on at least one surface of the lithium metal layer, wherein the oxide layer has cracked regions and non-cracked regions.

[0053] In this invention, a "cracked region" in the oxide layer can refer to a region in the oxide layer whose thickness is less than that of a "non-cracked region" in the adjacent oxide layer. For example, a "non-cracked region" can refer to a region in the oxide layer with a larger thickness, and a "cracked region" can refer to a region in the oxide layer whose thickness is less than that of the adjacent "non-cracked region". Specifically, a "cracked region" can refer to a region equal to or less than 50%, 40%, 30%, 20%, or 10% of the oxide layer thickness (i.e., the maximum thickness of the oxide layer of lithium metal) of the "non-cracked region". Alternatively, a "cracked region" can refer to an exposed area of ​​the lithium metal layer where no oxide layer exists.

[0054] Figure 10 This is a cross-sectional view of a lithium metal anode according to one embodiment of the present invention. Figure 11 This is a detailed cross-sectional view of a lithium metal anode according to one embodiment of the present invention.

[0055] Reference Figure 10 and Figure 11 An oxide layer 20 is disposed on one surface of the lithium metal layer 10, and the oxide layer 20 has a cracked region 30 and a non-cracked region 40. The cracked region 30 can be an area equal to or less than 50% of the maximum thickness of the oxide layer of lithium metal. Furthermore, the cracked region 30 can refer to an exposed area of ​​the lithium metal layer 10 where no oxide layer exists. Meanwhile, because the surface of the oxide layer cannot be completely flat, areas with small height differences on the oxide layer surface may not be cracked regions. For example, the height of the non-cracked region 50 is lower than the height of the thickest part of the oxide layer, but it differs from the cracked region 30.

[0056] Figure 10 and Figure 11 A cross-section of a lithium metal anode according to one embodiment of the present invention is shown, and the lithium metal anode of the present invention is not limited to... Figure 10 and Figure 11 The structure. For example, although Figure 10 and Figure 11 The diagram shows an oxide layer on one surface of the lithium metal layer, but according to another embodiment of the invention, the oxide layer may be disposed on both surfaces of the lithium metal layer.

[0057] In this invention, a "cracked region" may include depressions, pores, openings, and trenches on the surface of the oxide layer. Furthermore, the depth of the cracked region may refer to the height difference perpendicular to the lithium metal surface from the highest point of the oxide layer on the lithium metal surface to the lowest point of the cracked region. For example, if the highest thickness of the oxide layer on the lithium metal surface is 100 nm and the thickness of the oxide layer remaining in the cracked region is 5 nm, the depth of the cracked region may be 95 nm.

[0058] Furthermore, because the surface of the oxide layer cannot be completely smooth, the crack zone is not an area with a small height difference on the oxide layer surface. That is, the crack zone can refer only to areas with a depth of at least 20 nm or 30 nm.

[0059] Furthermore, the depth of the crack zone can be equal to or greater than 60%, 70%, 80%, or 90% of the thickness of the oxide layer, and since the oxide layer is completely removed in the crack zone, the crack zone does not have an oxide layer. In this case, the depth of the crack zone can be 100% of the thickness of the oxide layer.

[0060] In this invention, a "cracked area" can refer to an area without oxides in an image observed by scanning electron microscopy (SEM) at 30,000× magnification. Alternatively, a "cracked area" can refer to a black area or an area darker than the adjacent "non-cracked area" in an image observed by SEM at 30,000× magnification. Conversely, a "non-cracked area" can appear white or brighter than the adjacent cracked area. In this case, SEM imaging can be performed immediately after heat treatment, after battery formation, or before battery cycling, but is not limited thereto. Furthermore, SEM observation is performed from the top of the lithium metal anode surface and is a vertical (top-down) observation of a plane parallel to the oxide layer and lithium metal. When observing the SEM image with the naked eye, the "cracked area" and "non-cracked area" can be identified as black areas or areas darker than the adjacent areas, and white areas or areas brighter than the adjacent areas, respectively.

[0061] The areas of cracked and non-cracked regions can be more clearly distinguished by converting the SEM-observed image into a binary image. Specifically, the areas of cracked and non-cracked regions can be more clearly distinguished by converting the SEM-observed image into white and black.

[0062] For example, the raw image observed by SEM can be converted into a binary image through thresholding. Here, thresholding can include global thresholding, Otsu thresholding, or adaptive thresholding.

[0063] Set a global threshold and replace pixel values ​​above the threshold with black, and pixel values ​​below the threshold with white.

[0064] Otsu thresholding uses the Otsu algorithm to generate binary images. The Otsu algorithm iteratively divides the pixels of a binary image into two classes based on an arbitrarily set threshold and identifies the intensity distribution of each class. Then, among all possible thresholds, it selects the one that results in the most uniform intensity distribution between the two classes. The Otsu algorithm automatically finds the optimal threshold.

[0065] Adaptive thresholding involves dividing the image into regions and calculating a threshold while converting the image into a binary image using only adjacent pixel values. High-quality binary images can be generated through adaptive thresholding when the original image contains different background colors or a variety of colors that make it difficult to generate a clear binary image using a single threshold.

[0066] In one embodiment of the invention, the area ratio of the cracked region to the non-cracked region can be calculated using an image of the oxide layer surface observed by SEM. For example, after dividing the cracked region and the non-cracked region using the method described above, a boundary line between the cracked region and the non-cracked region can be set, and the areas of the cracked region and the non-cracked region can be measured, and the area ratio of the cracked region to the non-cracked region can be calculated. In this case, the boundary line between the cracked region and the non-cracked region can be set to clearly distinguish the boundary between white or bright areas and black or gray areas in the SEM image. Meanwhile, because there is a small height difference in the non-cracked region of the oxide layer, the non-cracked region can have very bright parts and less bright parts. Since, as used herein, a cracked region refers to an area equal to or less than a predetermined percentage thickness of the oxide layer in the non-cracked region, although very bright parts and less bright parts are observed in the non-cracked region, this is due to the small height difference within the non-cracked region. Therefore, the less bright parts should be considered as non-cracked regions, and because they are less bright, they should not be considered as cracked regions.

[0067] In one embodiment of the invention, the non-cracked region may be formed at least one "oxide island" in the non-cracked region surrounded by the cracked region. In this case, the oxide island (non-cracked region) may refer to a region with a thickness equal to the maximum thickness of the oxide layer, or equal to or greater than 90%, 80%, 70%, 60%, or 50% of the maximum thickness of the oxide layer in the region surrounded by the cracked region. For example, the "oxide island" may be an oxide layer region (non-cracked region) with a thickness of 100 to 120 nm, and may be surrounded by an oxide region (cracked region) with a thickness of less than 5 nm.

[0068] In one embodiment of the invention, in an image observed by SEM at 30,000× magnification, "oxide islands" (i.e., non-cracked areas) may appear white or a brighter color than adjacent cracked areas. Conversely, oxide defect areas (i.e., cracked areas) surrounding the "oxide islands" may appear black or a darker color than adjacent non-cracked areas. In this case, SEM observation can be performed immediately after heat treatment of the lithium metal anode, after battery assembly, or before battery cycling, but is not limited thereto. Furthermore, the SEM observation is a top-down (vertical) observation of the lithium metal anode surface, parallel to the oxide layer and the lithium metal.

[0069] In one embodiment of the invention, the oxide layer may be a lithium oxide layer. Furthermore, the oxide layer may be an intrinsic oxide layer. An intrinsic oxide layer is formed on a metal surface through a reaction between the metal and an air component. The intrinsic oxide layer of lithium typically has a bilayer structure. In this bilayer structure, the inner layer may be lithium oxide (Li₂O), and the outer layer may be lithium hydroxide (LiOH) and lithium carbonate (Li₂CO₃). Additionally, lithium metal can react with nitrogen to form lithium nitride (Li₃N), therefore the intrinsic oxide layer of lithium may include lithium nitride. However, the constituent materials of the lithium oxide layer are not limited to the materials described above and may include various materials applicable to those skilled in the art.

[0070] In one embodiment of the present invention, the lithium metal anode has a crack region in the oxide layer on the lithium metal surface, and the oxide layer present on the lithium metal surface can be partially removed or destroyed. Due to the crack region, the thick oxide layer, which acts as an obstacle to lithium insertion / extraction, is completely or partially removed or destroyed, exposing the lithium metal or reducing the thickness of the oxide layer, thereby reducing the overvoltage required for lithium insertion / extraction and thus improving lithium insertion / extraction. Furthermore, during electrodeposition, the crack region can serve as a lithium nucleation site, and due to the presence of the crack region, the surface area of ​​the lithium metal surface increases, and the surface electric field decreases, thereby suppressing dendrite growth and forming a uniform electrodeposition.

[0071] In one embodiment of the present invention, the oxide layer may have cracked and non-cracked regions, and the area ratio of the cracked to the non-cracked regions may be 2:8 to 9:1 or 4:6 to 6:4. When the area ratio of the cracked to the non-cracked regions meets the above range, it is easier to improve lithium insertion / extraction, achieve uniform electrodeposition, and suppress dendrite growth, thereby contributing to improved battery life. The area of ​​the cracked and non-cracked regions can be calculated from the image of the oxide layer observed by SEM.

[0072] In one embodiment of the invention, at least part or all of the crack region may be of a thin and elongated shape, and the average width of the crack region may be 1 to 500 nm, 10 to 400 nm or 50 to 300 nm.

[0073] In one embodiment of the present invention, at least part or all of the crack region may be of a thin and long shape, and the average length of the crack region may be more than 2.5 μm or more than 3 μm.

[0074] In one embodiment of the present invention, at least part or all of the vertical cross-section of the crack region may be a thin and long shape, and the ratio of the average length to the average width of the crack region may be 0.001 to 0.2, 0.01 to 0.2 or 0.03 to 0.2.

[0075] The term "long shape" as used in this article should be broadly understood to mean a shape with different diameters in different vertical directions, such as a non-spherical shape, i.e., an ellipse. Furthermore, the shape is not limited to ellipses, rectangles, or wavy shapes, and may include irregular shapes.

[0076] The length of the crack zone is the distance between the two farthest points of the crack zone, and can be determined using an image of lithium metal with an oxide layer observed by SEM. Specifically, the length of the crack zone can be determined using an image of the electrode surface observed by SEM. More specifically, the length of the crack zone can be determined using an image of the crack zone observed on the surface.

[0077] The width of the crack zone refers to the distance between the oxide layers on one side and the other side of the crack zone in a direction perpendicular to an imaginary straight line connecting the two furthest points of the crack zone, and can be determined using an image of lithium metal with oxide layers observed by SEM. Specifically, the width of the crack zone can be determined using an image of the crack zone observed on the electrode surface when viewed by SEM.

[0078] According to one embodiment of the present invention, the total thickness of the oxide layer can be from 10 nm to 10 μm, or from 20 nm to 1 μm. That is, for example, the thickness of the non-cracked region of the oxide layer can meet the above range. When the thickness of the oxide layer meets the above range, it is easier to prevent degradation during lithium metal storage and to prevent the problem of lithium deintercalation / extraction failure due to high resistance.

[0079] According to one embodiment of the present invention, the lithium metal layer can be in the form of a sheet, foil, or film. Furthermore, the thickness of the lithium metal layer can be 1 to 200 μm, or 5 to 100 μm. When the thickness of the lithium metal layer meets the above ranges, it is easier to provide a lithium source sufficient for battery operation and to achieve high energy density.

[0080] The lithium metal anode of one embodiment of the present invention can be manufactured by the following methods, but is not limited thereto.

[0081] According to one aspect of the present invention, a method for preparing a lithium metal anode comprising a lithium metal layer and an oxide layer on at least one surface of the lithium metal layer includes forming a crack region in the oxide layer.

[0082] In one embodiment of the present invention, a crack region can be formed in the oxide layer formed on the surface of lithium metal by heat treatment of lithium metal. The crack region can be formed in the oxide layer present on the surface of lithium metal by the volume expansion of lithium metal during the heat treatment process.

[0083] In one embodiment of the present invention, a crack zone can be formed in the oxide layer formed on the surface of lithium metal by heat-treating lithium metal at temperatures of 40°C to 120°C, 60°C to 100°C, or 65°C to 85°C. When the temperature conditions for heat treatment of lithium metal meet the above conditions, a crack zone can be sufficiently formed in the oxide layer on the surface of lithium metal, and the reduction in thickness of lithium metal and lithium anode active material due to lithium evaporation can be prevented, thereby further improving the lifespan of the electrochemical device containing the lithium metal anode.

[0084] In one embodiment of the invention, crack zones can be formed in the oxide layer formed on the surface of lithium metal by heat-treating lithium metal in a vacuum atmosphere at a pressure of 0.001 to 1 Torr. When lithium metal is heat-treated under the above pressure conditions and vacuum atmosphere, it is easier to prevent the further formation of an oxide layer through the reaction of residual gas with the lithium metal surface. In addition, it is easier to prevent the immediate reaction of lithium metal exposed in the crack zone with residual gas to form an oxide layer again when a crack zone is formed during heat treatment.

[0085] In another embodiment of the invention, crack zones can be formed in the oxide layer formed on the surface of lithium metal by heat-treating lithium metal in an inert atmosphere. Here, the inert gas forming the inert atmosphere refers to a gas that does not cause a chemical reaction, such as argon and nitrogen, and is not limited to the aforementioned gases, but includes any gas that can be applied by those skilled in the art. When lithium metal is heat-treated in an inert atmosphere, it is easier to prevent the further formation of an oxide layer through the reaction of residual gas with the lithium metal surface. Additionally, it is easier to prevent the immediate reaction of the exposed lithium metal or the thinned oxide layer with residual gas during the heat treatment process when a crack zone is formed, thus preventing the re-formation of an oxide layer.

[0086] In one embodiment of the invention, cracks can be formed in the oxide layer formed on the surface of lithium metal by heat-treating lithium metal at a temperature of 40°C to 120°C or 60°C to 100°C in a vacuum atmosphere with a pressure of 0.001 to 1 Torr.

[0087] In another embodiment of the invention, cracks can be formed in the oxide layer formed on the surface of lithium metal by heat-treating lithium metal in an inert atmosphere at a temperature of 40°C to 120°C or 60°C to 100°C.

[0088] An electrochemical device according to one embodiment of the present invention comprises a lithium metal anode having an oxide layer with cracks on its surface to improve lifespan.

[0089] The electrochemical device of the present invention includes all devices that cause electrochemical reactions, and specific examples include any one of a primary battery, a secondary battery, a fuel cell, a solar cell, or a capacitor such as a supercapacitor.

[0090] In one embodiment of the invention, the electrochemical device may include any lithium secondary battery that typically uses lithium metal as the negative electrode and is used in the relevant field, and may be a lithium-ion battery, a lithium-sulfur battery, or a lithium-lithium symmetric cell.

[0091] An electrochemical device according to one embodiment of the present invention includes a positive electrode, a lithium metal negative electrode, a separator, and a non-aqueous electrolyte solution. The electrochemical device can be engineered by placing the positive and negative electrode surfaces opposite each other, inserting the separator therein, and injecting the non-aqueous electrolyte solution.

[0092] The positive electrode, the diaphragm, and the non-aqueous electrolyte solution in an electrochemical device according to one embodiment of the present invention will be described in more detail below.

[0093] The positive electrode comprises a positive electrode active material, a binder, and a conductive material. The positive electrode active material may include materials commonly used in electrochemical devices, and for example, may include lithium nickel cobalt manganese compounds (lithium NCM compounds) and may include elemental sulfur (S8), sulfur compounds, or mixtures thereof. Specifically, the sulfur compound may be Li2S. n (n≥1), organic sulfur compounds or carbon-sulfur complexes ((C2S) x ) n(x = 2.5 to 50, n ≥ 2). Additionally, the positive electrode active material may include a sulfur-carbon composite, and since sulfur alone is not conductive, it can be used in combination with conductive materials. The carbon material (or carbon source) constituting the sulfur-carbon composite may include any carbon material with a porous structure or high specific surface area commonly used in the relevant field. Porous carbon materials may include, for example: graphite; graphene; carbon black, including Denka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermally cracked carbon black; carbon nanotubes (CNTs), including single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); carbon fibers, including graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs); activated carbon; or two or more of these, but not limited to, and their shape is not limited to a specific shape, and may include any shape applicable to electrochemical devices, such as spherical, rod-shaped, needle-shaped, sheet-like, tubular, or block-shaped.

[0094] Furthermore, carbon materials possess porosity, ranging from 40% to 90%, or 60% to 80%. When the porosity meets these ranges, lithium-ion transport can be easily improved, and a decrease in mechanical strength can be prevented. The pore size of carbon materials can range from 10 nm to 5 μm, or 50 nm to 5 μm. When the pore size of carbon materials meets these ranges, lithium-ion permeability can be easily improved, and battery short circuits and safety issues caused by contact between electrodes can be prevented.

[0095] The adhesive is a component that assists in bonding the positive electrode active material to the conductive material and to the current collector, and may include, for example, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF / HFP), polyvinyl acetate, polyvinyl alcohol, polyvinyl ether, polyethylene, polyethylene oxide, alkylated polyethylene oxide, polypropylene, poly(meth)acrylate, poly(meth)acrylate, polytetrafluoroethylene (PTFE), polyvinyl chloride, polyacrylonitrile, polyvinylpyridine, polyvinylpyrrolidone, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene monomer (EPDM) rubber, sulfonated EPDM rubber, styrene-butene rubber, fluororubber, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, or two or more of these, but is not necessarily limited thereto.

[0096] Based on 100 parts by weight (i.e., the total weight of the positive electrode), the amount of binder added is typically 1 to 50 parts by weight, or 3 to 15 parts by weight. When the binder content meets the above range, it is easy to ensure the adhesion between the positive electrode active material and the current collector and to guarantee the battery capacity.

[0097] The conductive material contained in the positive electrode is not limited to a specific type and may include any kind of conductive material that has high conductivity without causing side reactions in the internal environment of the electrochemical device and without causing chemical changes in the corresponding battery. It may typically include: graphite or conductive carbon, such as graphite, including natural and artificial graphite; carbon black, including carbon black, acetylene black, Ketjen black, Denka black, thermally cracked carbon black, channel black, furnace black, lamp black, and thermally cracked carbon black; carbonaceous materials having a graphene or graphite crystal structure; conductive fibers, including carbon fibers and metal fibers; fluorocarbons; metal powders, including aluminum powder and nickel powder; conductive whiskers, including zinc oxide and potassium titanate; conductive oxides, including titanium oxide; conductive polymers, including polyphenylene derivatives; or two or more of these, but not limited to them.

[0098] Based on 100 parts by weight (i.e., the total weight of the positive electrode), the amount of conductive material added can typically be 0.5 to 50 parts by weight, or 1 to 30 parts by weight. When the amount of conductive material meets the above range, conductivity can be easily improved, electrochemical properties can be prevented from deteriorating, and the capacity and energy density of the positive electrode can be guaranteed.

[0099] The method of incorporating conductive material into the positive electrode is not limited to a specific method, and conventional methods known in the art can be used, such as coating onto the positive electrode active material. Additionally, if necessary, a conductive second coating can be added to the positive electrode active material instead of the conductive material.

[0100] Optionally, a filler may be added to the positive electrode of the present invention to suppress positive electrode expansion. The filler is not limited to a specific type and may include any type of filler that can suppress electrode expansion without causing chemical changes in the battery, for example, it may include: olefin polymers, including polyethylene and polypropylene; fibrous materials, including glass fiber and carbon fiber; and so on.

[0101] The positive electrode can be manufactured by dispersing and mixing positive electrode active materials, binders, and conductive materials in a dispersion medium (solvent) to prepare a slurry, coating the slurry onto a positive electrode current collector, and then drying and rolling it. The dispersion medium may include, but is not limited to, N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), ethanol, isopropanol, water, and mixtures thereof.

[0102] Positive electrode current collectors can include platinum (Pt), gold (Au), palladium (Pd), iridium (Ir), silver (Ag), ruthenium (Ru), nickel (Ni), stainless steel (STS), aluminum (Al), molybdenum (Mo), chromium (Cr), carbon (C), titanium (Ti), tungsten (W), indium-doped SnO2 (ITO), fuchsinium-doped SnO2 (FTO), and their alloys, as well as aluminum (Al) or stainless steel surface-treated with carbon (C), nickel (Ni), titanium (Ti), or silver (Ag), but are not necessarily limited to these. Positive electrode current collectors can take the form of foil, film, sheet, stamped part, porous body, foam, etc.

[0103] A separator can be inserted between the positive and negative electrodes. The separator is a physical membrane that functions to physically separate the electrodes, and can include any separator commonly used in this art without limitation; particularly, it is preferred to be any separator that has low resistance to ion migration in the electrolyte solution and high electrolyte solution wettability. Additionally, the separator allows lithium ions to migrate between the positive and negative electrodes while simultaneously separating or insulating them. The separator can be made of porous, non-conductive, or insulating materials. The separator can be a standalone component, such as a membrane, or a coating added to the positive and / or negative electrodes.

[0104] Examples of polyolefin porous membranes that can be used as diaphragms may include membranes made of polyethylene, such as high-density polyethylene, linear low-density polyethylene, low-density polyethylene, and ultra-high molecular weight polyethylene, polypropylene, polybutene, and polypentene, used alone or in combination. Examples of nonwoven fabrics that can be used as diaphragms may include nonwoven fabrics made of polyphenylene ether, polyimide, polyamide, polycarbonate, polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyphenylene sulfide, polyacetal, polyethersulfone, polyetheretherketone, and polyester, used alone or in combination. Nonwoven fabrics may be made of fibers forming a porous web and may include spunbond or meltblown forms of long fibers.

[0105] The thickness of the separator can be from 1 to 100 μm, or from 5 to 50 μm, but is not limited to these. When the separator thickness meets the above range, it is easy to maintain the mechanical properties and prevent the battery performance from deteriorating due to the separator acting as a resistive layer. The pore size and porosity of the separator can be from 0.1 to 50 μm and from 10% to 95%, respectively, but are not limited to these. When the pore size of the separator meets the above range, it is easy to prevent the separator from acting as a resistive film and maintain the mechanical properties of the separator.

[0106] The non-aqueous electrolyte may contain: a first solvent comprising a heterocyclic compound having or not having at least one double bond and containing at least one of oxygen or sulfur atoms; a second solvent comprising at least one of ether, ester, amide, or carbonate compounds; a lithium salt; and lithium nitrate.

[0107] The first solvent, the second solvent, the lithium salt, and the lithium nitrate contained in a non-aqueous electrolyte solution according to one embodiment of the present invention will be described in detail below.

[0108] First solvent

[0109] The first solvent comprises a heterocyclic compound having or not having at least one double bond, and containing at least one of oxygen or sulfur atoms. Because the delocalization of the lone pair electrons of the heteroatoms (oxygen or sulfur) makes the salt difficult to dissolve, a solid electrolyte interface (SEI) layer formed on the lithium metal surface by the ring-opening reaction of the heterocyclic compound during the initial discharge step of the battery can suppress the formation of lithium dendrites and reduce the decomposition of the electrolyte solution on the lithium metal surface and subsequent side reactions, thereby improving the lifespan characteristics of the electrochemical device.

[0110] That is, the heterocyclic compound of the present invention may contain more than one double bond to form a polymer protective film on the lithium metal surface, and definitively contains at least one polar heteroatom (oxygen atom or sulfur atom) to improve affinity with other solvents in the electrolyte solution.

[0111] Heterocyclic compounds may include 3- to 15-membered heterocyclic compounds, 3- to 7-membered heterocyclic compounds, or 5- to 6-membered heterocyclic compounds. Furthermore, heterocyclic compounds may include unsubstituted or substituted heterocyclic compounds, or those substituted with at least one selected from the group consisting of an alkyl group having 1 to 4 carbon atoms, a cycloalkyl group having 3 to 8 carbon atoms, an aryl group having 6 to 10 carbon atoms, a halogen group, a nitro group (-NO2), an amino group (-NH2), and a sulfonyl group (-SO2). Additionally, heterocyclic compounds may be polycyclic compounds of at least one heterocyclic compound having 3 to 8 carbon atoms or an aryl group having 6 to 10 carbon atoms.

[0112] When heterocyclic compounds are substituted with alkyl groups having 1 to 4 carbon atoms, the free radicals are stabilized, thereby suppressing side reactions in the electrolyte solution. Furthermore, when heterocyclic compounds are substituted with halogen or nitro groups, a functional protective film can be formed on the lithium metal surface, and in this case, the formed functional protective film can be a stable and compact protective film. Additionally, lithium metal can be deposited uniformly. In particular, when the electrochemical device is a lithium-sulfur battery, side reactions between polysulfides and lithium metal can be suppressed.

[0113] Specific examples of heterocyclic compounds may include 1,3-dioxolane, 4,5-diethyl-1,3-dioxolane, 4,5-dimethyl-1,3-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, 4-methyl-1,3-dioxane, 2-methyl-1,3-dioxane, furan, 2-methylfuran, 3-methylfuran, 2-ethyl 2-Propylfuran, 2-Butylfuran, 2,3-Dimethylfuran, 2,4-Dimethylfuran, 2,5-Dimethylfuran, pyran, 2-Methylpyran, 3-Methylpyran, 4-Methylpyran, benzofuran, 2-(2-nitrovinyl)furan, thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-Dimethylthiophene, 2,4-Dimethylthiophene, and 2,5-Dimethylthiophene.

[0114] Based on 100% by volume of the non-aqueous electrolyte solution of one embodiment of the present invention, all organic solvents (i.e., first solvent + second solvent) are contained therein. The content of the first solvent, which contains heterocyclic compounds, can be from 5% to 50% by volume (the remainder corresponding to the second solvent). When the amount of the first solvent meets the above range, it is easy to prevent the problem of imperfect formation of a protective film on the lithium metal surface, and to prevent the problem of reduced battery capacity and life due to increased surface resistance of the electrolyte solution and lithium metal.

[0115] In particular, when the positive electrode active material is sulfur, it is easier to prevent the problem of reduced ability to reduce the solubility of polysulfides, which would otherwise make it difficult to suppress the increase in resistance of the electrolyte solution.

[0116] Second solvent

[0117] The second solvent may include at least one of ether compounds, ester compounds, amide compounds, or carbonate compounds, and can be used not only to dissolve lithium salts to give the electrolyte solution lithium-ion conductivity, but also to dissolve the positive electrode active material to promote the electrochemical reaction with lithium. In particular, when the positive electrode active material is sulfur, the second solvent can be used to dissolve sulfur as the positive electrode active material, thereby promoting the electrochemical reaction with lithium.

[0118] Carbonate compounds can be linear carbonate compounds or cyclic carbonate compounds.

[0119] Specific examples of ether compounds may include dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, polyethylene glycol methyl ethyl ether, or two or more of these, but are not limited thereto.

[0120] In addition, ester compounds may include, for example, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, ε-caprolactone, or two or more of these, but are not limited thereto.

[0121] Amide compounds can be those commonly used in this technical field.

[0122] Linear carbonate compounds may include, for example, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), or two or more of these, but are not limited thereto.

[0123] Cyclic carbonate compounds may include, for example, ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentene carbonate, 2,3-pentene carbonate, vinylene carbonate, vinyl ethylene carbonate, their halides (such as fluoroethylene carbonate (FEC), etc.), or two or more of them, but are not limited thereto.

[0124] Based on 100% by volume of the non-aqueous electrolyte solution of one embodiment of the present invention, all organic solvents (i.e., first solvent + second solvent) are contained, wherein the content of the second solvent can be from 50% to 95% by volume. When the amount of the second solvent meets the above range, the lithium salt can be sufficiently dissolved, thereby easily preventing the problem of decreased lithium-ion conductivity and easily preventing the deposition of positive electrode active material exceeding the soluble concentration. In particular, when the positive electrode active material is sulfur, it is easy to prevent the deposition of sulfur as the positive electrode active material exceeding the soluble concentration, and it is easy to prevent the problem of increased shuttle phenomenon between lithium polysulfides and lithium metal anode due to excessive dissolution of sulfur and shortened lifespan.

[0125] Meanwhile, based on 100% by weight of all non-aqueous electrolyte solutions according to one embodiment of the present invention, the content of the organic solvent comprising the first solvent and the second solvent can be 60% by weight to 99.5% by weight, 60% by weight to 99% by weight, 60% by weight to 98% by weight, or 60% by weight to 95% by weight. When the amount of organic solvent meets the above ranges, it is easy to prevent the problem of increased viscosity and decreased ionic conductivity of the electrolyte solution, or the problem of lithium salt or additives not being completely dissolved in the electrolyte solution, and it is also easy to prevent the problem of decreased ionic conductivity due to low lithium salt concentration in the electrolyte solution.

[0126] lithium salts

[0127] Lithium salts are electrolyte salts used to improve ionic conductivity and may include, for example, LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB. 10 Cl 10 LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (C2F5SO2)2NLi, (SO2F)2NLi (i.e., LiFSI), (CF3SO2)2NLi (i.e., LiTFSI), (CF3SO2)3CLi, lithium chloroborane, lower aliphatic carboxylic acids having 4 or fewer carbon atoms, lithium tetraphenylborate, lithium imide, or two or more of these.

[0128] The concentration of the lithium salt can be determined by taking into account ionic conductivity and can be, for example, 0.2 to 2 M, or 0.5 to 1 M. When the concentration of the lithium salt meets the above range, it is easy to ensure ionic conductivity suitable for battery operation and to suppress the decrease in lithium ion migration due to the increase in the viscosity of the electrolyte solution, or to prevent an increase in the decomposition reaction of the lithium salt itself.

[0129] Lithium nitrate

[0130] In one embodiment of the present invention, the non-aqueous electrolyte solution may include lithium nitrate (LiNO3). Lithium nitrate reacts with the lithium metal anode to form a lithiophilic protective film, such as lithium nitride (Li3N) and lithium oxynitride (LiON), on the surface of the lithium metal anode. This inhibits lithium dendrite growth and prevents the decomposition of electrolyte components, thereby improving battery life and efficiency.

[0131] In addition, if necessary, it may further contain lanthanum nitrate (La(NO3)3), potassium nitrate (KNO3), cesium nitrate (CsNO3), magnesium nitrate (Mg(NO3)2), barium nitrate (Ba(NO3)2), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), or two or more of them.

[0132] Based on a 100% by weight total non-aqueous electrolyte solution, the lithium nitrate content can be from 0.1% to 7% by weight, 0.5% to 5% by weight, or 0.5% to 1.5% by weight. When the amount of lithium nitrate meets the above ranges, it is easy to prevent a sharp decrease in coulombic efficiency and an increase in the viscosity of the electrolyte solution.

[0133] In one embodiment of the present invention, the non-aqueous electrolyte solution may contain 1,3-dioxolane as a first solvent, dimethoxyethane as a second solvent, (CF3SO2)2NLi as a lithium salt, and lithium nitrate. 1,3-dioxolane and dimethoxyethane can have high lithium polysulfide solubility and stabilize the lithium metal anode. Therefore, when the non-aqueous electrolyte solution contains the above materials, the electrochemical device can exhibit optimal characteristics.

[0134] Meanwhile, the lithium secondary battery of one embodiment of the present invention can be used as a battery cell for use as a power source for small devices, and is particularly suitable for use as a unit cell in a battery module for powering medium to large devices. In this regard, the present invention also provides a battery module comprising two or more electrochemical devices electrically connected to each other (in series or in parallel). Obviously, the number of electrochemical devices contained in the battery module can be adjusted in various ways depending on the intended use and capacity of the battery module. Additionally, the present invention provides a battery pack comprising battery modules electrically connected to each other by common methods. The battery modules and battery pack can be used as a power source for at least one medium to large device, such as power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); electric trucks; electric commercial vehicles; or energy storage systems, but the present invention is not necessarily limited thereto.

[0135] In the following description, embodiments of the present invention will be detailed to aid in understanding the invention. However, embodiments of the present invention may be implemented in many different forms and the scope of the invention should not be construed as limited to the following embodiments. Embodiments of the present invention are provided to explain the invention more completely to those skilled in the art.

[0136] Example 1-1

[0137] A 35 μm thick lithium metal anode was obtained by heat-treating it for 4 hours at 40 °C in a convection oven under a vacuum atmosphere at 0.01 Torr and then rolling it onto one surface of a copper current collector.

[0138] Examples 1-2

[0139] The lithium metal anode was manufactured in the same manner as in Example 1-1, except that the heat treatment was performed at a temperature of 60°C.

[0140] Examples 1-3

[0141] The lithium metal anode was manufactured in the same manner as in Example 1-1, except that the heat treatment was performed at a temperature of 80°C.

[0142] Examples 1-4

[0143] The lithium metal anode was manufactured in the same manner as in Examples 1-1, except that the heat treatment was performed at a temperature of 100°C.

[0144] Examples 1-5

[0145] The lithium metal anode was manufactured in the same manner as in Example 1-1, except that the heat treatment was performed at a temperature of 120°C.

[0146] Comparative Example 1-1

[0147] A 35μm thick layer of lithium metal is used as the lithium metal anode without any treatment.

[0148] Examples 2-1 to 2-5 and Comparative Example 2-1: Manufacturing of Lithium-Lithium Symmetric Cells

[0149] First, based on the total weight of the electrolyte solution, 1% by weight of lithium nitrate is added to an organic solvent comprising 1,3-dioxolane (first solvent) and dimethoxyethane (second solvent) in a volume mixing ratio (v / v) of 1:1, and (CF3SO2)2NLi(LiTFSI) (lithium salt) is dissolved to a concentration of 1M, thereby preparing a non-aqueous electrolyte solution.

[0150] The lithium metal anodes manufactured in Examples 1-1 to 1-5 and Comparative Example 1-1 were used as positive and negative electrodes respectively, and in this case, the lithium electrodes were placed opposite each other. Subsequently, a 16 μm thick porous polyethylene (PE) membrane was placed between the positive and negative electrodes, and the prepared non-aqueous electrolyte was injected and sealed to manufacture a coin cell type lithium-lithium symmetric cell.

[0151] Examples 3-1 to 3-5 and Comparative Example 3-1: Manufacturing of Lithium-Sulfur Batteries

[0152] First, a positive electrode slurry composition was prepared by mixing 87.5 parts by weight of a sulfur-carbon (CNT) composite (S / C weight ratio 75:25) as the positive electrode active material, 5 parts by weight of Denka Black as the conductive material, and 7.5 parts by weight of a styrene-butadiene rubber / carboxymethyl cellulose (SBR / CMC 7:3) as a binder. The positive electrode slurry composition was then applied to one surface of a current collector (Al foil), dried at 80°C, and pressed using a roller press to manufacture the positive electrode (in this case, the loading was 4.5 mg / cm³). 2 ).

[0153] Then, the positive electrode and the lithium metal negative electrode manufactured in Examples 1-1 to 1-5 and Comparative Example 1-1 are placed opposite each other, a porous polyethylene (PE) separator is placed in the middle, and the non-aqueous electrolyte prepared in Examples 2-1 to 2-5 and Comparative Example 2-1 is injected and sealed to manufacture a coin cell type lithium-sulfur battery.

[0154] Evaluation Example 1: Surface observation of lithium metal anode

[0155] The surfaces of the lithium metal anodes manufactured in Examples 1-3 and Comparative Example 1-1 were observed using scanning electron microscopy (SEM), and were respectively... Figure 1 and Figure 2 As shown in the figure. In this case, the lithium metal anodes manufactured in Examples 1-3 were immediately subjected to SEM observation after heat treatment. The SEM equipment used was a JEOL JSM-7200F with a magnification of 30,000× and an accelerating voltage of 5kV. Furthermore, the resolution of the equipment used was 1nm at 20kV, 1.6nm at 1kV, and therefore 1 to 1.6nm at 5kV.

[0156] Depend on Figure 2 As can be seen, in the lithium metal anode manufactured in Comparative Example 1-1, the lithium metal surface is covered with an intrinsic oxide layer without any cracked areas.

[0157] On the contrary, by Figure 1 As can be seen, in the lithium metal anodes manufactured in Examples 1-3, crack regions are formed in the oxide layer present on the lithium metal surface.

[0158] Evaluation Example 2: Calculate the area ratio of the cracked region to the non-cracked region in a lithium metal anode.

[0159] The area ratio of the cracked region to the non-cracked region was calculated using SEM images of the lithium metal anode surfaces manufactured in Examples 1-1 to 1-5 and Comparative Example 1-1. The SEM used was a JEOL JSM-7200F with a magnification of 30,000× and an accelerating voltage of 5 kV. Furthermore, the resolution of the device was 1 nm at 20 kV and 1.6 nm at 1 kV, therefore 1 to 1.6 nm at 5 kV.

[0160] Specifically, in images observed via SEM, non-cracked areas appear brighter due to their rough and uneven surfaces, while cracked areas appear darker due to their smooth surfaces. To utilize this property, the SEM images were converted to binary images using ImageJ software. The colors in the binary images were then interchanged, turning white into black and vice versa, thereby maximizing brightness and making non-cracked areas appear darker and cracked areas appear brighter. The area ratio was then calculated using the areas of the cracked and non-cracked areas, and the results are shown in Table 1 below.

[0161] [Table 1]

[0162] Example 1-1 40 2:8 Examples 1-2 60 4:6 Examples 1-3 80 5:5 Examples 1-4 100 6:4 Examples 1-5 120 9:1 Comparative Example 1-1 - -

[0163] Evaluation Example 3: Cycle Life Assessment of Lithium-Lithium Symmetric Cells

[0164] In the lithium-lithium symmetric cells manufactured in Examples 2-1 to 2-5 and Comparative Example 2-1, the temperature was increased to 1.5 mA / cm² at 25°C. 2 The current density was repeatedly subjected to discharge (lower limit -1V) and charge (upper limit +1V) cycles to measure the potential change over time (cycles), and the cycle life was evaluated and shown in Table 2 below. Figures 3 to 8 As shown in the table, when the lithium anode operates smoothly during symmetrical cell operation, the overvoltage level is 0.1V. However, when the lithium anode deteriorates, a larger overvoltage is required for lithium deintercalation. The requirement of -1V overvoltage indicates the lithium deintercalation / deintercalation difference at the lithium anode, thus indicating that the lithium anode is not functioning properly. Table 2 summarizes the cell lifespan when the required overvoltage for lithium deintercalation / deintercalation is -1V.

[0165] [Table 2]

[0166] Example 2-1 40 13 Example 2-2 60 23 Example 2-3 80 31 Examples 2-4 100 29 Examples 2-5 120 21 Comparative Example 2-1 - 9

[0167] From Table 1 and Table 2 and Figures 3 to 8As can be seen, compared to the lithium-lithium symmetric cell manufactured in Comparative Example 2-1, which does not have cracked regions in the oxide layer on the lithium metal surface, the lithium-lithium symmetric cells manufactured in Examples 2-1 to 2-5 exhibit improved cycle life due to the uniform electrodeposition caused by the cracked regions formed in the oxide layer on the lithium metal surface. In particular, the battery life is further improved in the lithium-lithium symmetric cells manufactured in Examples 2-2 to 2-4 at heat treatment temperatures of 60°C to 100°C.

[0168] Evaluation Example 4: Cycle Life Assessment of Lithium-Sulfur Batteries

[0169] In the lithium-sulfur batteries manufactured in Examples 3-1 to 3-5 and Comparative Example 3-1, 0.2C charge / 0.3C discharge cycles were performed in CC mode at 25°C within a voltage range of 1.8 to 2.5V, thereby measuring the capacity-potential with each charge / discharge cycle (initially 2.5 cycles at 0.1C / 0.1C, stabilizing at 0.2C / 0.2C for 3 cycles, and operating at 0.3C / 0.5C from the 7th cycle onwards). The results are shown in Table 3 below. Figure 9 As shown in the image.

[0170] [Table 3]

[0171] Example 3-1 40 107 Example 3-2 60 158 Example 3-3 80 186 Examples 3-4 100 172 Examples 3-5 120 118 Comparative Example 3-1 - 83

[0172] From Table 3 and Figure 9 As can be seen, compared to the lithium-sulfur battery obtained in Comparative Example 3-1 which did not have cracked regions in the oxide layer on the lithium metal surface, the lithium-sulfur batteries manufactured in Examples 3-1 to 3-5, which included an oxide layer with cracked regions on the lithium metal surface, exhibited improved cycle life. Furthermore, the lithium-sulfur batteries manufactured in Examples 3-2 to 3-4 at heat treatment temperatures of 60 to 100°C showed further improvements in battery life. In particular, the lithium-sulfur battery manufactured in Example 3-3 at a heat treatment temperature of 70 to 90°C exhibited a significantly improved lifespan.

Claims

1. A lithium metal anode, comprising: Lithium metal layer; and An oxide layer on at least one surface of the lithium metal layer, in, The oxide layer has cracked and non-cracked regions. Wherein, the thickness of the cracked region in the oxide layer is equal to or less than 50% of the maximum thickness of the oxide layer, and The area ratio of the cracked region to the non-cracked region is 2:8 to 9:

1.

2. The lithium metal anode as described in claim 1, wherein, The area ratio of the cracked region to the non-cracked region is 4:6 to 6:

4.

3. The lithium metal anode as described in claim 1, wherein, The thickness of the cracked region in the oxide layer is equal to or less than 40% of the maximum thickness of the oxide layer.

4. The lithium metal anode as described in claim 1, wherein, The thickness of the oxide layer is 10 nm to 10 μm.

5. The lithium metal anode as described in claim 1, wherein, The thickness of the lithium metal layer is from 1 μm to 200 μm.

6. A method for manufacturing the lithium metal anode of claim 1, the lithium metal anode comprising a lithium metal layer and an oxide layer on at least one surface of the lithium metal layer, the method comprising: Crack zones are formed in the oxide layer.

7. The method for manufacturing a lithium metal anode as described in claim 6, wherein, The formation of the cracked region involves heat-treating the lithium metal anode in a vacuum atmosphere at a pressure of 0.001 to 1 Torr.

8. The method for manufacturing a lithium metal anode as described in claim 6, wherein, The formation of the cracked region involves heat-treating the lithium metal anode in an inert atmosphere.

9. The method for manufacturing a lithium metal anode as described in claim 6, wherein, The formation of the cracked region involves heat-treating the lithium metal anode at a temperature of 40°C to 120°C.

10. The method for manufacturing a lithium metal anode as described in claim 6, wherein, The formation of the cracked region involves heat-treating the lithium metal anode at 65°C to 85°C.

11. An electrochemical device comprising a lithium metal anode according to any one of claims 1 to 5.

12. The electrochemical device of claim 11, wherein, The electrochemical device includes a lithium secondary battery.

13. The electrochemical device of claim 12, wherein, The lithium secondary battery includes at least one of lithium-ion batteries, lithium-sulfur batteries, or lithium-lithium symmetrical cells.

Citation Information

Patent Citations

  • Change of opening and closing direction of self ligation orthodontic bracket

    KR1020220004911A

  • Protected electrode structures

    US20210135192A1